SISTEM INFORMASI ADMINISTRASI PENJUALAN DAN PERSEDIAAN BARANG PADA DIMSUM BANG ANDRI DENGAN MODEL WATERFALL BERBASIS WEB - Josua (2022)
Information system are a significant part of the development of information technology in the world. The need for technology triggers rapid technological developments. The development of information technology affects human performance to solve problems that exist in the world. The research was conducted to create web-based sales and inventory administration information system for Dimsum Bang Andri's business. Sales transaction in this business still use the traditional way. This makes sales transaction ineffective because sales transaction must be carried out with confirmation of inventory. In addition, sales report are also not generated. The purpose of this research is to create a system that can help sales transaction at Dimsum Bang Andri. In this study, researchers used the waterfall model with a system built using PHP programming language and codeigniter framework supported by MySQL database. The result of this research is an information system that can be used by Dimsum Bang Andri business owners to speed up the sales transaction process, manage sales data, and inventory data